Pengembangan Media Pembelajaran Interaktif Konfigurasi Elektron Elektronik Otomatis Mata Pelajaran IPA Di Masa Pandemi Covid-19 - Yayuk Dian Mandasari; M. Subandowo; Wawan Gunawan (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
The purpose of this development is to create an interactive learning media for Automatic Electronic Electronic Configuration based on Articulate Storyline that is feasible and effective to use to achieve maximum student learning outcomes in science subjects with class IX electron configuration material at SMP Negeri 1 Wonoayu Sidoarjo during the COVID-19 pandemic. 19. The product is in the form of an Html5 application for ONLINE learning and flash/CD for OFFLINE learning. This study utilizes the ADDIE development model which consists of five interrelated stages, namely Analysis, Design, Development, Implementation, and Evaluation. The results of the development of interactive learning media for Automatic Electronic Electronic Configuration based on the assessment of content experts on average 98.95%, media experts 89.73%, and design experts 92.26%. The assessment belongs to the very good criteria and the very feasible category. The results of the expert's assessment are relevant to the impact of learning on student learning outcomes which show classical completeness of 88.13%.AbstrakTujuan dari pengembangan ini yaitu menciptakan media pembelajaran interaktif Konfigurasi Elektron Elektronik Otomatis yang berbasis Articulate Storyline yang layak serta efektif digunakan untuk mencapai hasil belajar peserta didik secara maksimal pada mata pelajaran IPA dengan materi konfigurasi elektron kelas IX SMP Negeri 1 Wonoayu Sidoarjo di masa pandemi COVID- 19. Produk berbentuk aplikasi Html5 pada pembelajaran DARING dan flashdisk/CD untuk pembelajaran LURING. Penelitian ini memanfaatkan model pengembangan ADDIE yang terdiri dari lima tahapan yang saling berkaitan, yaitu Analysis, Design, Development, Implementation, dan Evaluation. Hasil Pengembangan media pembelajaran interaktif Konfigurasi Elektron Elektronik Otomatis berdasarkan penilaian ahli isi rata-rata sebesar 98,95%, ahli media 89,73%, dan ahli desain 92,26%. Penilaian tersebut tergolong dalam kriteria yang sangat baik dan kategori yang sangat layak. Hasil penilaian para ahli relevan dengan dampak pembelajaran terhadap hasil belajar peserta didik yang menunjukkan ketuntasan klasikal sebesar 88,13%.